Modeling the ductile damage process in commercially pure titanium. (August 2016) - Zhai, Jinyuan; Luo, Tuo; Gao, Xiaosheng; Graham, Stephen M.; Baral, Madhav; Korkolis, Yannis P.; Knudsen, Erik
Abstract: This paper presents a constitutive model, which combines the models proposed by Stewart and Cazacu (2011) and Zhou et al. (2014), to describe the ductile damage process in a commercially pure titanium (CP Ti) and to simulate its mechanical response. In particular, a Gurson-type porous material model is modified by coupling two damage parameters, accounting for the void damage and the shear damage respectively, into the yield function and the flow potential. The plastic anisotropy and tension–compression asymmetry exhibited by CP Ti are accounted for by a plasticity model based on the linear transformation of the stress deviator. The theoretical model is implemented in the general purpose finite element software ABAQUS via a user defined subroutine and calibrated using experimental data. Good comparisons are observed between model predictions and experimental results for a series of specimens in different orientations and experiencing a wide range of stress states.